The prince : the secret story of the world's most intriguing royal, prince bandar bin sultan - Simpson, William ([S.l.] : William Morrow Paperbacks, 2008)
For the last two and a half decades$1 (Bthrough war, oil crises, and global terrorism$1 (Bthe United States and Saudi Arabia have had a very special relationship, thanks in no small part to one man: Prince Bandar bin Sultan. The illegitimate son of a Saudi prince and a servant girl, he used his vital behind-the-scenes influence to convince Gorbachev to withdraw the Soviet military from Afghanistan and helped President Reagan and CIA Director William Casey to win the Cold War with Saudi petrodollars. A Machiavellian manipulator, he negotiated an end to the Iran-Iraq war and played a key role in the Iran-Contra affair. George H. W. Bush took Bandar and his family fishing. Colin Powell would drop by to play racquetball. In this revealing biography, William Simpson pulls back the curtain on the fascinating and startling life of an extraordinary power-player who emerged as one of the driving forces behind American foreign policy throughout the 1980s and '90s. At a time when understanding our friends is as important as knowing our enemies, understanding Prince Bandar bin Sultan may well be the key to figuring out the Saudis.s